La odiseica «Eneida» de las Metamorfosis - Álvarez Morán, Mª Consuelo; Iglesias Montiel , Rosa Mª (Cuadernos de Filología Clásica. Estudios Latinos, 2009)
Ovid’s intertextual relationship with virgil is not passive but palam mutuandi causa. The authors of this paper revise the three Ovidian techniques of composition proposed by Galinsky: deliberate reduction, without competing with vergil, but with complementariness and allusion; parallelism in stories of similar length, with the complementariness as the main objective; and two manners of enlargement: addition of some passages absent in the Aeneid that are taken from other sources, and inclusion of original Ovidian episodes. This third technique could be said to be the most important, as it provides Ovid with a means for displaying his own reading of Homer, just as vergil did with the Odyssey. All three techniques are illustrated in this paper, especially the third one. This technique is present in the two love triangles with Circe as protagonist. In the «odysseyc Aeneid» Ovid corrects vergil by means of using Homer and other models, achieving an original composition. Macareus is presented as a kind of Ovid who, free from the Greek model, is endowed with a capacity for invention: he creates a narrator, Circe’s slave, and thus becomes the creator of someone who is able to create, that is, his text suggests the mimesis of the narrative.
Keywords: Metamorphoses; Odyssey; Aeneid; Intertextuality; Narrative Technique; Originality